Influence of Different Enamel Pretreatment on Bond Strength of Fissure Sealant - Dafina Doberdoli; Hrvoje Jurić (Acta Stomatologica Croatica)
Objective: The aim of this in vitro study was to evaluate the bond strength of a resin composite fissure sealant to enamel which was pre-treated with different laser pulse modes and additional acid etching. Materials and Methods: Forty-two healthy molars and premolars were collected for this study and randomly divided into 6 groups (n=7). Group 1: Quantum Square Pulse (QSP); Group 2: Medium-Short Pulse (MSP) mode; Group 3: Super Short Pulse (SSP) mode; Group 4: QSP + acid etching; Group 5: MSP + acid etching; Group 6: SSP + acid etching. The occlusal surfaces of the teeth were pretreated according to the defined group. Laser conditioning of the enamel was performed using an Er:YAG laser Fotona Light Walker AT-S (Fotona, Ljubljana, Slovenia) with a wavelength of 2940 nm + acid etching (EN etch Ivoclar Vivadent AG, Schaan, Liechtenstein). Occlusal surfaces were sealed with a resin-based composite fissure sealant (Helioseal F, Ivoclar Vivadent AG, Schaan, Liechtenstein). Micro-tensile bond strength (μTBS) test and stereomicroscope evaluations of the failure mode were performed. The μTBS was tested using the Games-Howell method. The failure mode between groups was tested using the chi-square test. The significance level for all tests was set at p <0.05. Results: The highest bond strength was measured using laser etching in MSP mode combined with acid etching (36.09 MPa). This combination showed a significantly higher bond strength than the other combinations (SSP + ETCH, p<0.001; QSP + ETCH, p<0.001). Conclusion: The SP laser followed by acid etching of enamel yielded the highest bond strength. Thus, the MSP with a 140 μs pulse mode might be the preferred choice as a pre-treatment procedure for fissure sealing.